Corporate finance : theory and practice - Vernimmen, Pierre (Wiley, 2017)
"Corporate Finance: Theory and Practice continues to hold sway as one of the most popular financial textbooks, thanks to its four unique features: A balanced blend of theory and practice: authors hold academic positions at top ranking universities and business schools and are also investment bankers, private investors or sit on the boards of listed and unlisted companies A presentation of concepts that explain situations, followed by a discussion of techniques in a direct and succinct style Content enriched by the www.vernimmen.com website, which with 1,500 daily visitors is one of the leading finance teaching sites worldwide Free monthly updates on finance through The Vernimmen.com Newsletter, with over 60,000 subscribers The authors draw on their dual experience to enhance and expand the content of this new, fifth edition to reflect the latest developments, in particular, the change to accounting for operating leases under both IFRS and US GAAP which will take place in 2018. The numerous statistical tables and graphs throughout the text are fully updated with the latest available information"- Resumé vydavatel
Revised edition of Corporate finance, 2014.
Includes index.
Keywords: finance podniku; finanční management; business finance; financial management; elektronické knihy; učebnice; electronic books; textbooks